2020
DOI: 10.1016/j.jsps.2020.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of knowledge of Alzheimer disease among health university students in Riyadh, Saudi Arabia

Abstract: Objective To assess the knowledge of Alzheimer disease among healthcare students of King Saud University, Riyadh Saudi Arabia. Methods This cross-sectional survey was conducted via an online questionnaire using google form as the main platform to collect the data. We included Pharmacy, medical and dental students, who are studying at king Saud University, Riyadh Saudi Arabia during February to March 2019. Results A total of 671 healthcare stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…A 23-item questionnaire regarding the knowledge and perception of the Pfizer-BioNTech COVID-19 vaccine was developed after an extensive review of the available literature. 26–31 …”
Section: Methodsmentioning
confidence: 99%
“…A 23-item questionnaire regarding the knowledge and perception of the Pfizer-BioNTech COVID-19 vaccine was developed after an extensive review of the available literature. 26–31 …”
Section: Methodsmentioning
confidence: 99%
“…As well as behavioral changes and eventually a decrease in the ability to do the simplest tasks (Ballard et al, 2011;Breijyeh & Karaman, 2020;Studart Neto & Nitrini, 2016). Alzheimer's disease is a rising health problem, with an estimated 6.4% in Saudi Arabia (al Arifi, 2020) and it has been linked with many risks' factors that contribute to the development and progression of disease such as aging, genetic defects, infections, vascular diseases and environmental factors (Alhumaidi et al, 2020;Breijyeh & Karaman, 2020). AD is most prevalent in individuals aged 60 years and most cases of Alzheimer's disease are sporadic.…”
Section: Medical Science L Analysis Articlementioning
confidence: 99%
“…Previous studies from different countries evaluated the knowledge regarding AD among college students and appeared to be below moderate (Baral et al, 2020). However, a study in Riyadh city revealed that the knowledge regarding Alzheimer's was varied among healthcare students with medical students having the highest knowledge level (al Arifi, 2020). Raising the knowledge of medical students is critical to improving the quality of life of people diagnosed with AD.…”
Section: Medical Science L Analysis Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Salah satu upaya yang dapat dilakukan untuk mengurangi beban perawatan dan manajemen penyakit baik untuk pasien dan keluarga adalah dengan mengurangi ketidaktahuan tentang penyakit alzheimer (Nagle et al, 2013). Oleh sebab itu pengetahuan dalam mengelola penyakit sangat penting bagi seluruh masyarakat (Arifi, 2020). Tindakan yang dapat meningkatkan pengetahuan masyarakat adalah dengan melakukan promosi kesehatan dengan pendidikan kesehatan.…”
Section: Pendahuluanunclassified